Effect of post-annealing on the properties of Co-doped ZnO thin films deposited by channel-spark ablation. (September 2018) - Ali, Asghar; Henda, Redhouane
Abstract: In this study, we report on the effect of post-annealing treatment on the structure and morphology of Co-doped ZnO (CZO) thin film nano-composites deposited on Si (100) by channel-spark pulsed electron beam ablation (PEBA) from a single target, Cox Zn1-x O (x = 0.20). The as-grown CZO films have been deposited within the temperature range 350 °C–450 °C, at electron beam acceleration voltages of 15 kV and 16 kV, and a beam frequency of 4 Hz. The films have been subjected to thermal annealing at either 400 °C or 600 °C for one hour. The effect of post-growth annealing on film properties has been discussed in terms of surface morphology, chemical composition, chemical state, and crystal structure. Experimental results show that, overall, post-annealing treatment significantly affects the structural and morphological properties of the films. Films annealed at 400 °C have higher average particle size and degree of crystallinity of ZnO hexagonal wurtzite structure relatively to the films annealed at 600 °C. Films annealed at 400 °C exhibit larger content in hexagonal close-packed (hcp) metallic Co (Co°) compared to the films annealed at 600 °C and to as-grown films. Both x-ray diffraction (XRD) and x-ray photoelectron spectroscopy (XPS) indicate that enhanced growth of Co о is achieved at the annealing temperature of 400° C.